リュツォ・ホルムワン イキ ヲ チュウシン トシタ エンガン ロガン タイリク ヒョウショウ カイヒョウ ヒョウメン ケイタイ ノ コウクウキ チョウサ ホウコク 1996-1998 (JARE-38) - 金尾, 政紀; カナオ, マサキ; 山内, 恭; ヤマノウチ, タカシ; Kanao, Masaki; Yamanouchi, Takashi (2000)
P(論文) 第38次日本南極地域観測隊(以下JARE-38と略す)の越冬期間中において, 地学研究部門を中心に固定翼航空機(セスナ式A185型)を用いた種々の地学・雪氷学的な予察調査・偵察飛行を実施した。主なフライトとしては, リュツォ・ホルム湾地域の積雪, 氷状の季節変化を調べるための沿岸露岩域の空撮を行い, 表層地形・地質構造との相関を調べることで, 越冬期間における地上での現地調査のための基礎資料とした。また, 大陸氷床上みずほHルート東側にある裸氷帯およびモレーンの調査を実施し, 将来の地学・雪氷探査のための基礎資料の収集を行った。さらに, 昭和基地周辺の大陸氷床上において, JAREにおける将来の大型航空機導入のための滑走路候補地の調査も行った。他に氷状偵察等を含め, 関連のJARE-38越冬期間中のフライトは, 計15回, 43時間55分に達した。さらに, 往復路のアムンゼン湾調査では, 「しらせ」搭載のヘリコプター(シコルスキーS-61A型)を用いて, 主に湾周辺の雪氷環境を調べ, 将来の人工地震探査の測線の候補地を選んだ。これらのフライトにより, 地震探査や大型航空機の導入など, 観測・設営の両面において, 今後の南極観測における貴重な資料が得られた。 Preliminary airbone surveys for geoscientific and glaciological purposes were carried out by an aircraft (Cessna A185F) during the wintering season of the 38th Japanese Antarctic Research Expedition (JARE-38) in 1996-1998. First, several flights were conducted to investigate the relationship between snow-covered area and geological structure/topography on some outcrop surfaces along the Soya Coast and in the Prins Olav Coast region. Second, inland flights on the continental ice sheet were carried out to survey the surface conditions of bared blue ice and moraine areas on the Mizuho Plateau, about 50km eastward of the H-route. Then future prospects for geophysical and glaciological research were investigated. Moreover, feasibility surveys to determine the proper position of the airfield in the vicinity of Syowa Station were carried out in order to establish snow-ice runways for large aircraft for JARE in future. The recommended positions are located 1) near S16 and 2) eastward of the Langhovde region, where surface altitudes on the continental ice sheet are around 500m. In addition, surveys were carried out to detect changes of sea-ice distribution during the winter and to locate snow-vehicle routes in Lutzow-Holm Bay. Fifteen flights with a total of 43h55m flight hours were made for the present purpose in the whole season of JARE-38. Moreover, the surveys around the Amundsen Bay region were carried out using "Sikorsky S61A" helicopters of the icebreaker "Shirase" to decide ...